Evaluation of application potential of used cooking oils in the synthesis of polyol compounds. Issue 6 (December 2019) - Kurańska, Maria; Banaś, Joanna; Polaczek, Krzysztof; Banaś, Marian; Prociak, Aleksander; Kuc, Joanna; Uram, Katarzyna; Lubera, Tomasz
Abstract: According to a new trend related with the circular economy, it is necessary to develop new chemical components based on waste. Used cooking oil (UCO) constitutes an economic and environmental alternative for fresh vegetable oil used in the synthesis of epoxidized oil and polyol. Ten different samples of UCO were collected from local restaurants and their physical and chemical properties were evaluated. The samples were studied by the means of infrared spectroscopy and gel permeation chromatography, and also by determination of the acid, iodine, peroxide, p-anisidine and viscosity values as well as in terms of the presence of polycyclic aromatic hydrocarbons and polychlorinated biphenyls. The UCO samples were characterized by acid values in the range of 1.50–5.21 mgKOH/g and iodine values of 105.7–111.9 gI2 /100 g, which is interesting in terms of a potential modification of the oils by the two-step method of epoxidation and oxirane ring opening. Our analysis of the oil properties showed that these materials cannot be reused for food purposes due to oxidative changes confirmed by high peroxide and anisidine values, as well as the presence of polycyclic aromatic hydrocarbons and polychlorinated biphenyls. The most informative indicator describing the susceptibility of oil to oxidation is the parameter TOTOX which in this experiment was in the range 60.5–141.7 for UCOs and 4.7 for the reference oil. However, this research shows that such municipal waste can be used in the synthesis of epoxidized oil and bio-polyol. The properties of the bio-components based on UCO were comparable to the properties of the epoxidized oil and polyols obtained from the fresh rapeseed oil which was used as a reference sample. The epoxy value of the modified UCO was in the range of 0.30-0.33 mol/100 g and for the modified rapeseed oil it was 0.34 mol/100 g. UCO offers potential industrial applications in the field of the synthesis of bio-components for the preparation of polymeric materials.